Vaginal Delivery in Placental Abruption: Persalinan Pervaginam pada Solusi Plasenta - JM Seno Adjie; M Farid Ghazali; Denny Khusen (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To describe the case of vaginal delivery in placental abruption. Methods: A case report Results: In the case of placental abruption, we could perform vaginal delivery. Conclusion: The treatment of placental abruption can be vaginally or by cesarean section depending on the severity of disease, gestational age, and state of the mother and fetus. Keywords: IUFD, placental abruption, vaginal delivery